PENEGAKAN HUKUM PELANGGARAN PEMASANGAN ALAT PERAGA KAMPANYE PADA PEMILLIHAN UMUM 2024 DI KABUPATEN PASAMAN BARAT: Tinjauan Berdasarkan Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum - Arif Budiman; Hasnul Arifin Melayu; Rispalman Rispalman (Journal of Indonesian Comparative of Syari'ah Law, 2025)
With the General Election, people can take part in determining the direction of the State. Elections are organised by the General Election Commission (KPU) which is then assisted by the Election Supervisory Body (BAWASLU) to create elections in accordance with what is mandated by the Legislation. General elections cannot be separated from the regulations that must be obeyed so that the implementation of elections can run in an orderly manner, but in fact the implementation of elections has not been running with what is mandated by the Legislation, the campaign period is very much found violations in the field, especially regarding the installation of Campaign Props that violate the rules, West Pasaman Bawaslu found 1560 violations regarding the installation of Campaign Props which must be followed up in order to create clean elections from all violations, especially regarding the installation of violating Campaign Props. The law enforcement carried out by Bawaslu Pasaman Barat includes giving sanctions of reprimand and taking action against violations by disciplining campaign props, while this research method uses empirical juridical by paying attention to the implementation of laws or rules in the field and the implementation of elections in West Pasaman Regency.